2003
DOI: 10.1002/ijc.10937
|View full text |Cite
|
Sign up to set email alerts
|

CYP enzyme polymorphisms and susceptibility to HCV‐related chronic liver disease and liver cancer

Abstract: Cancer risk can be influenced by the exposure to endogenous or environmental toxins. Polymorphic enzymes involved in the metabolic activation/detoxification of carcinogens may account for individual variations of risk. We studied the polymorphisms of five enzymes of the P450 superfamily, CYP1A1, CYP1A2, CYP2D6, CYP2E1 and CY3A4, as risk factors for liver disease progression and cancer in hepatitis C virusinfected patients. CYP genotyping was performed by polymerase chain reaction (PCR) restriction fragment len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 60 publications
3
37
0
1
Order By: Relevance
“…In contrast, in agreement with our present results, some reports also showed no association between certain EME polymorphism and risk for hepatocellular carcinoma. For instance, no association of the two CYP1A1 polymorphisms, MspI and Ile462Val, was observed with the hepatocellular carcinoma risk in either chronic hepatitis B carriers or hepatitis C virus -infected patients (29,30). It was also reported that the CYP17 MspAI and COMT Val158Met are not associated with the risk for hepatitis C virus -related hepatocellular carcinoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in agreement with our present results, some reports also showed no association between certain EME polymorphism and risk for hepatocellular carcinoma. For instance, no association of the two CYP1A1 polymorphisms, MspI and Ile462Val, was observed with the hepatocellular carcinoma risk in either chronic hepatitis B carriers or hepatitis C virus -infected patients (29,30). It was also reported that the CYP17 MspAI and COMT Val158Met are not associated with the risk for hepatitis C virus -related hepatocellular carcinoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports of genetic polymorphisms associated with HCC in patients with chronic HCV infection include the Ϫ31Ϫ511/T-C haplotype in the promoter region of the gene for the proinflammatory cytokine IL-1␤ in the Japanese population (11), polymorphisms in the microsomal epoxide hydrolase gene in Italians (14), and polymorphisms in the enzyme cytochrome P in Caucasians (12). Although we failed to find a SNP map that predicted high susceptibility to HCC in this study, accumulating information on HCC-related SNPs may facilitate the identification of patients with high susceptibility to HCC in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Recently, we reported that genetic polymorphisms in interleukin-1␤ 11 and uridine 5Ј-diphosphate-glucuronosyltransferase 1A7 12 are associated with the development of HCC in Japanese patients with chronic HCV infection. Genetic polymorphisms in CYP enzymes, 13 the microsomal epoxide hydrolase gene, 14 and the aldehyde dehydrogenase 2 gene 15 also have been reported to be associated with HCC and the severity of HCV-related liver disease. The number of candidate genes that have been examined is, however, rather limited.…”
mentioning
confidence: 99%